Africa’s food security requires accurate trade statistics - Bouët, Antoine; Cissé, Brahima; Traoré, Fousseini (2021)
Mark Twain once warned, “There are three kinds of lies: lies, damned lies, and statistics.” Yet statistics are a fundamental tool for economic and decision-making by governments, international institutions, and even the private sector. International trade statistics play a particularly important role. They allow us to determine a country's current account balance — that is, whether a country is living above or below its means — which is crucial information for macroeconomic policy. Detailed information on trade flows can be used to identify not only a country’s largest trading partners, but also the sectors in which it has a comparative advantage or disadvantage. This makes it possible to design structural actions to improve the competitiveness of certain sectors or trade relations with certain countries. These same statistics also provide valuable information for the private sector, as they help in identifying both attractive sectors for investment and which countries offer promising markets or are emerging as serious competitors.